(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
Police departments around the world are embracing new predictive policing technology that will help them spot criminals before the crime takes place. Predictive analysis provides tools that have the potential to improve the efficiency of law enforcement, however, this outcome ultimately depends on the human beings’ understanding of the inherent limitations of such tools in order to avoid ineffective and unfair results. This brief analysis seeks to highlight the potential risks arising from the use of predictive policing, with specific reference to the processing of personal data, the lack of algorithm transparency and the discriminatory consequences.